The New Myths of Speculative Fiction Cinema: How Mythical Thought is Returning in the Contemporary World - Silva, Marco Fraga (Ação Midiática – Estudos em Comunicação, Sociedade e Cultura, 2020)
This paper argues that the decline of myth and mythical thought is reversing and that the substitute of ancient myth in modern societies – politics – has been replaced by the speculative fiction genre of cinematic storytelling. With this in mind the paper creates a link between: our species ability to tell stories and our necessity to consume them; the importance and characteristics of myth and mythical thought; the human craving for mythical stories; the contemporary speculative fjction trend worldwide in the box offjce; and a study of the most infmuential fjlms of all time.